2021
DOI: 10.1186/s12943-020-01302-6
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow infiltrated natural killer cells predicted the anti-leukemia activity of MCL1 or BCL2 inhibitors in acute myeloid leukemia

Abstract: Acute myeloid leukemia (AML) is still incurable due to its heterogeneity and complexity of tumor microenvironment. It is imperative therefore to understand the molecular pathogenesis of AML and identify leukemia-associated biomarkers to formulate effective treatment strategies. Here, we systematically analyzed the clinical characters and natural killer (NK) cells portion in seventy newly-diagnosis (ND) AML patients. We found that the proportion of NK cells in the bone marrow of ND-AML patients could predict th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…In a similar approach, we have recently shown that Smac mimetics may synergize with NK cell-mediated killing [ 49 ]. Preliminary indications that BH3 mimetics may modulate NK cell attack have been provided by a recent report indicating that the Mcl-1 inhibitor maritoclax may cooperate with NK cells to kill leukemia cells [ 50 ]. However, maritoclax may exert additional cellular functions unrelated to the inhibition of Mcl-1 and has been shown to induce cell death also in cells lacking Mcl-1 by induction of reactive oxygen species [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a similar approach, we have recently shown that Smac mimetics may synergize with NK cell-mediated killing [ 49 ]. Preliminary indications that BH3 mimetics may modulate NK cell attack have been provided by a recent report indicating that the Mcl-1 inhibitor maritoclax may cooperate with NK cells to kill leukemia cells [ 50 ]. However, maritoclax may exert additional cellular functions unrelated to the inhibition of Mcl-1 and has been shown to induce cell death also in cells lacking Mcl-1 by induction of reactive oxygen species [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was well demonstrated that NK cells function in tumor immunosurveillance as they can kill cancer cells without prior sensitization (39)(40)(41). As a kind of important tumor-infiltrating lymphocytes (TILs), low-expressed NK cells are discovered on multiple cancers, which are linked with a poor prognosis of patients, too (42,43). A single cell sequencing study of lung GGO and solid nodules concluded that NK cell cytotoxicity was lower in solid nodules, which showed that the function of the NK cell decreased during the progression of lung adenocarcinoma (44).…”
Section: Discussionmentioning
confidence: 99%
“…The study further showed that AML exosomes could reprogram NK-92 cells, interfering with their anti-leukemia functions and reducing the therapeutic potential of adoptive cell transfers (91). Recently, Dai et al proposed that the proportion of NK cells in the BM of AML could predict patient prognosis, with a lower proportion of NK cells associated with worse prognosis (92).…”
Section: Immunosuppressive Factors In the Tumor Microenvironment Bone Marrow Microenvironment In Leukemiamentioning
confidence: 99%